PHIL Migration to Internal Carotid Artery and Middle Cerebral Artery: Late Mechanical Retrieval with Solitaire AB Stent - Saal-Zapata, Giancarlo; Durand, Walter; Vallejos, Ricardo; Valer, Dante; Flores, Jesús; Rodriguez, Rodolfo (Journal of Clinical Interventional Radiology ISVIR, 2020)
Precipitating hydrophobic injecting liquid (PHIL) is a novel embolic agent used in the endovascular treatment of arteriovenous malformations (AVM) and arteriovenous fistulas. Complications can occur during embolization with migration of the liquid embolic material to normal vasculature. In these cases, use of a stent retriever is an option for removal of the plug. Herein, we present the case of a patient who presented with a right occipital hemorrhage due to a ruptured occipital AVM fed by the calcarine and parieto-occipital arteries with venous drainage to the straight sinus. Embolization via the anterior circulation through the right posterior communicating artery was attempted but PHIL migrated to right internal carotid artery and middle cerebral artery due to kinking and rupture of the microcatheter. The patient developed mild left hemiparesis. When this complication occurred, no stent retriever was available at our institution and 1 day later, the Solitaire AB stent was used to remove the plug of PHIL successfully, with good reperfusion of the proximal and distal vessels. The patient improved after the procedure and was discharged home without deficit. Mechanical stent retrievers can be used in cases of migration of liquid embolic agents to normal vasculature with good clinical and radiological results.
Keywords: PHIL; microcatheter; arteriovenous malformation